2003
DOI: 10.1046/j.1365-2141.2003.04259.x
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage depletion following liposomal‐encapsulated clodronate (LIP‐CLOD) injection enhances megakaryocytopoietic and thrombopoietic activities in mice

Abstract: Summary. Megakaryocytopoiesis is the cellular process by which stem cells progress through commitment, proliferation and differentiation, leading to the production of platelets. In the mouse, this process is accomplished within the bone marrow (BM) and spleen microenvironment and is carried out by regulatory molecules and accessory cells, including macrophages, fibroblasts and endothelial‐like cells. Previously, we demonstrated that specific macrophage depletion, using liposomal‐encapsulated clodronate (LIP‐CL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Our findings are consistent with and add to previous reports of Mϕ−dependent impairment of megakaryopoiesis and platelet production at steady state. 46,47 Additionally, macrophage-colony stimulating factor M-CSF, a factor that increases Mϕ self-renewal, transiently causes thrombocytopenia. 47 Our study builds upon these findings and identify Mϕs as key sensors or target cells of IFNγ.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with and add to previous reports of Mϕ−dependent impairment of megakaryopoiesis and platelet production at steady state. 46,47 Additionally, macrophage-colony stimulating factor M-CSF, a factor that increases Mϕ self-renewal, transiently causes thrombocytopenia. 47 Our study builds upon these findings and identify Mϕs as key sensors or target cells of IFNγ.…”
Section: Discussionmentioning
confidence: 99%
“…21 Of note, clodronate liposomes do not deplete platelets but rather increase thrombopoietic activities, excluding that the observed bleedings are caused by a loss of platelets. 22 In our previous study in nonanticoagulated mice, infarct hemorrhage after extensive macrophage depletion occurred between days 2 and 3 after stroke onset, 17 corresponding to the temporal risk profile delineated in our present study. This suggested that macrophage-dependent brain repair may be involved in the prevention of OAC-associated sICH.…”
Section: Discussionmentioning
confidence: 99%
“…(80) This is the result of no sequestering or destruction of platelets by the spleen, as well as a slight increase in platelet production in the bone marrow, (81) the latter possibly because splenic macrophages and other spleen stromal cell populations are involved in the regulation of platelet production. (82) Serious thromboembolic events can accompany splenectomy (pulmonary embolism, deep vein and portal vein thrombosis) and may be related to a procoagulant activity of substances released from circulating damaged erythrocytes.…”
Section: Other Functions Of the Spleenmentioning
confidence: 99%